Integrating AI in academic writing: Lecturers and students' experiences related to benefits and challenges - Andriyanti, Erna; Murtafi’ah, Banatul; Zudianto, Hardian; Rochma, Anis Firdatul; Tuilan, Jeane; Akhyari, Muhammad Wafa (English Education Department, Universitas Islam Indonesia, 2025)
The rapid development of Generative Artificial Intelligence (Gen AI) has influenced how English as a Foreign Language (EFL) learners and educators engage in academic writing. This study aims to explore how lecturers and students in Indonesian higher education integrate AI tools into their academic writing practices, perceive benefits and challenges of using AI, and concern with ethical considerations. Using a qualitative approach combining interviews and photovoice, the study involved thirteen participants from western, central, and eastern Indonesia. The findings show that AI tools are used not only for linguistic assistance but also for idea generation, prompt refinement, and collaborative meaning-making, reflecting an interactive relationship between users and technology. Participants reported that AI improves efficiency, creativity, and clarity in writing, while concerns were raised regarding hallucinated references, inconsistency, and overreliance that may reduce critical thinking and authenticity. The study also finds that AI should be used ethically as a complementary partner that supports, rather than replaces, human intellect in academic writing. The main ethical considerations include maintaining authorship, content verification, and proper referencing. The findings imply the need for pedagogical frameworks and institutional policies that promote ethical, reflective, and responsible AI use in higher education.